The Influence of Leadership Style, Competence and Work Motivation on Employee Performance at the Cirebon Regency Health Office - Hindriyani; Dharliana Ayu Hardjowikarto; Juwita (Journal Research of Social Science, Economics, and Management, 2026)
Employee performance in the public health sector remains a critical issue in Indonesia, particularly in regional health offices that face both structural and individual challenges. Internal evaluations at the Cirebon Regency Health Office revealed suboptimal performance, including delays in service delivery, inconsistencies in SOP implementation, and unmet Minimum Service Standards (SPM) targets. This study aims to examine the influence of leadership style, competence, and work motivation — both partially and simultaneously — on employee performance at the Cirebon Regency Health Office. The research employed a quantitative method with an associative/explanatory approach. Data were collected through a structured questionnaire distributed to 80 respondents selected via proportionate stratified random sampling from a total population of 100 employees. The Likert scale (1–5) was used to measure respondents' perceptions, and data were analyzed using multiple linear regression with SPSS 26, preceded by validity, reliability, and classical assumption tests. The coefficient of determination (R²) showed that 72.7% of the variation in employee performance was explained by the three variables. Partially, leadership style (? = 0.434, sig. = 0.009), competence (? = 0.229, sig. = 0.026), and work motivation (? = 0.493, sig. = 0.001) each had a positive and significant effect on employee performance. Simultaneously, the F-test confirmed a significant joint effect (F = 67.587, sig. = 0.000). Work motivation was the most dominant variable. Improving leadership quality, employee competence, and internal work motivation are key strategies for enhancing public health service performance at the regional level.